Realismo em Adorno e Lukács: o caso Em câmara lenta, de Renato Tapajós - Carlos Augusto Carneiro Costa (Estudos de Literatura Brasileira Contemporânea, 2012)
The first part of this work presents a study of the essays Introdução aos escritos estéticos de Marx and Engels, by Georg Lukács, and Posição do narrador no romance contemporâneo, by Theodor W. Adorno, in which we analyze their respective conceptions of realism in literature, considering their criteria of literary aesthetics valuation. The second part corresponds to the analysis of the Renato Tapajós’ novel Em câmara lenta (1977), in which we examine its formal constitution in the light of the notions of realism in question, trying to point a plausible theoretical basis for reading novels that, like Tapajós one, are formed by negativity.